Male Gaze and Feminist Counter-Narratives in Ancient and Contemporary Epic Literature - Adhikari, Tara Prasad (NPRC Journal of Multidisciplinary Research, 2025)
This paper compares the representation of Draupadi in Vyasa’s Mahabharata and Chitra Banerjee Divakaruni’s The Palace of Illusions through Laura Mulvey’s concept of the male gaze and feminist literary criticism. Draupadi’s body, in the epic, is repeatedly framed as a site of male rivalry, most starkly in the swayamvara, disrobing, and exile episodes. Conversely, The Palace of Illusions reclaims her agency by granting her narrative voice and agency. While Mulvey’s theory explains the mechanisms of Draupadi’s objectification, the analysis also situates her voice within postcolonial feminist debates on female agency. The study argues that Divakaruni’s retelling challenges the epic’s gendered discourse by presenting Draupadi as a subject rather than spectacle, thereby offering a feminist counter-narrative to patriarchal traditions.